Examination of the Clinical Utility of Eating Disorder and Disordered Eating Screening Tools in Young Athletes: A Scoping Review - Barbara J. Hoogenboom; Zachary Capulong; Megan Teeter (International Journal of Sports Physical Therapy)
# Background and Purpose